A service-life cycle approach to maintenance and energy retrofit planning for building portfolios. (August 2019) - Nägeli, Claudio; Farahani, Abolfazl; Österbring, Magnus; Dalenbäck, Jan-Olof; Wallbaum, Holger
Abstract: Residential buildings account for almost a quarter of the total energy use in Sweden and building owners are, therefore, under pressure from policy makers to improve the energy performance of their buildings. Building portfolio owners (BPOs) generally face multiple barriers in energy efficiency investments such as financial constraints and lack of knowledge of the current state when planning energy efficiency measures. This paper presents a method for cost-optimal scheduling of maintenance and retrofit measures on a portfolio level by drawing on research on building stock modeling and maintenance retrofit planning. The method uses a building stock modeling approach to model costs, energy and greenhouse gas emissions (GHG)of a building portfolio and combines this with a method for optimal maintenance and retrofit scheduling in order to forecast and optimize the timing of measures on a building portfolio level. This enables the integrated long-term planning on retrofit investments and reduction of energy demand and GHG emissions for a portfolio of existing buildings. The application to the building portfolio of the municipal housing company of Gothenburg showed that by optimizing the maintenance and retrofit plans, ambitious retrofit measures can be introduced in the majority of the buildings with a positive effect on the service-life cycle costs. Moreover, the method is easily transferable to other building portfolios in Sweden as it builds up on nationally available data sets but is ideally complemented and verified using inspection data and existing maintenance plans of the BPOs in future applications. Highlights: This paper presents a method for cost-optimal planning of maintenance and retrofit measures in portfolio level. The application of the method showed that retrofit measures can be applied in most buildings with a reduction of EAC. Through optimization, the total EAC of the retrofit scenario can be lowered by 15% compared to a reinstatement scenario. By applying an ambitious retrofit scenario, the average energy demand can be lowered from 120 to 65 kWh/m 2 year by 2050. The method is easily transferable to other building portfolios in Sweden as it builds up on national data sets.